(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article uses neural network technology for an intelligent measurement device that includes a database, knowledge base, and other blocks. The working principle, functional scheme and training algorithm of the intelligent measuring device have been developed based on neural networks. Temperature, density, and other uncertain parameters that affect the accuracy of the measuring device and the moisture content of the scattering materials are taken as control objects.